PATHOLOGICAL EFFECT OF LOW GRADE AFLATOXICITY IN BROILERS - RAMDAS, RATHOD PRAVIN; KULKARNI , GANGADHAR BALKRISHNA; GANGANE, GOVIND (The Bioscan, 2013)
Experimental mycotoxicoses was induced into broiler chickens by feeding 100 and 150 ppb aflatoxin from 0 to 45 days of age to evaluate the gross and histopathological changes. Grossly, the liver was enlarged, icteric, mottled soft and friable. Histopathologically, the liver showed hepatomegaly, focal necrosis, degenerative changes of hepatic cell, icteric mucous membranes, petechial haemorrhages, diffuse centrilobular necrosis, fatty change, chronic toxicity resulted in cirrhosis and bile duct hyperlpasia. Renal parenchyma showed degeneration and necrosis of tubules with focal lymphocytic infiltration in kidneys. In lungs shows congestion and oedema. Brain was showed occasional congestion & vacuolation. Spleen was congested and slightly increased in size. Bursa of fabricius was showed slight congestion throughout the study. Thus from above observations it was concluded that aflatoxin fed at 100 and 150 ppb have adverse effect on general health of broilers.